2021
DOI: 10.1002/essoar.10505376.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equitable Exchange: A framework for diversity and inclusion in the geosciences

Abstract:  We need new mechanisms to broaden participation in the geosciences  Co-production of science with local underrepresented communities may improve societal relevance and diversify geosciences  The Equitable Exchange creates an ethical framework for co-production and inculcates skills related to cultural competency and attention to inclusive practices into the geosciences

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The presented cases are a few of many examples in which ICON efforts are already common practices in observational and modeling data research and application among cryosphere studies. We identified that such integrated and interdisciplinary (I‐integrated) approaches to research questions bring new and powerful results with direct impacts on society (Harris et al., 2021). However, challenges are to continue developing standardized field and lab protocols (C‐coordinated) that allow comparison of data, benefit science of opportunities, and facilitate knowledge transfer (N‐networked).…”
Section: Observational and Modeling Data Research And Application In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The presented cases are a few of many examples in which ICON efforts are already common practices in observational and modeling data research and application among cryosphere studies. We identified that such integrated and interdisciplinary (I‐integrated) approaches to research questions bring new and powerful results with direct impacts on society (Harris et al., 2021). However, challenges are to continue developing standardized field and lab protocols (C‐coordinated) that allow comparison of data, benefit science of opportunities, and facilitate knowledge transfer (N‐networked).…”
Section: Observational and Modeling Data Research And Application In ...mentioning
confidence: 99%
“…However, we emphasize that alternatives to overcome such limitations should be prioritized (Settles et al., 2019). Indeed, researchers with diverse backgrounds could add more views on research gaps and thus increase chances for alternative out‐of‐the‐box solutions (Harris et al., 2021).…”
Section: Observational and Modeling Data Research And Application In ...mentioning
confidence: 99%
“…The goal is a healthy and supportive community in Earth and space sciences and recent progress reveals that many individuals are keen to help. The groundswell of interest is clear from contributions ranging from: strategies for individual and collective actions (Behl et al., 2021) to cultivate a more welcoming climate in the coastal, ocean, and marine sciences; to acknowledging the value of discussion groups (Ormand et al., 2021); to fostering the coproduction of research with local communities, such as the concept of “equitable exchanges” (Harris et al., 2021); and to documenting the altruistic motivations of young people poised to join our community (Carter et al., 2021). Of course, there is more, much more to be done in terms of racial/ethnic identity (Dutt, 2020), disabilities and access to the field (Atchison et al., 2019), and gender identity (Ranganathan et al., 2021), to name a few.…”
Section: What Can You Do To Achieve Regenerative Gatekeeping?mentioning
confidence: 99%
“…That is, a specific geographic place; often with a shared culture, heritage or lived experience; occasionally with a shared knowledge and skill set (i.e., a community of practice); and almost always underrepresented in and underserved by academic science. Under this definition, community science is an inherently local endeavor often mediated by a boundary spanner with one foot in the world of mainstream science and the other in community (Harris et al., 2021); where discovery science may take a back seat to actionable science; and where the work is co‐created by community members and science professionals willing to share the thought, work, and credit space.…”
Section: Figurementioning
confidence: 99%